Clinical trajectories of hand function impairment in systemic sclerosis: an unmet clinical need across disease subsets - Lorraine Green; Ariane L Herrick; Michelle Wilson; Francesco Del Galdo; Enrico De Lorenzis; Philip Helliwell; Benazir Saleem; Emma Derrett-Smith; Begonya Alcacer-Pitarch; Karen Douglas; Vishal Kakkar; Chris Denton; et al. (RMD Open)
Background Hand involvement is an early manifestation of systemic sclerosis (SSc), culprit of diagnosis and classification, and recognised major driver of disability. Impairment of hand function burdens both limited and diffuse cutaneous subsets and therefore could be targeted as ‘basket’ endpoint in SSc. Nevertheless, its natural history in current standard of care is not well characterised, limiting the design of targeted trials. The aim of this study is to describe prevalence, natural history and clinical factors associated with hand function deterioration in a longitudinal, multicentre, observational SSc cohort.Methods Hand function was captured through the validated Cochin Hand Function Scale in patients consecutively enrolled in a multicentre observational study and observed over 24 months. Minimal clinically important differences and patient acceptable symptom state were analysed as previously described.Results Three hundred and ninety-six consecutive patients were enrolled from 10 centres; 201 with complete follow-up data were included in the analysis. Median (IQR) disease duration was 5 (2–11) years. One hundred and five (52.2%) patients reported clinically significant worsening. Accordingly, the proportion of patients reporting unacceptable hand function increased over 2 years from 27.8% to 35.8% (p<0.001). Least absolute shrinkage and selection operator analysis identified male gender, disease subset, Raynaud’s Condition Score, tenosynovitis and pain, as some of the key factors associated with worsening hand involvement.Conclusions Hand function deteriorates over time in more than 50% of SSc patients despite available therapies. The analysis of factors associated with hand function worsening supports the involvement of both inflammation, vascular and fibrotic processes in hand involvement, making it a hallmark clinical manifestation of SSc. Our data are poised to inform the design of intervention studies to target this major driver of disability in SSc.